2022
DOI: 10.3390/ijms23105764
|View full text |Cite
|
Sign up to set email alerts
|

Small ORFs as New Regulators of Pri-miRNAs and miRNAs Expression in Human and Drosophila

Abstract: MicroRNAs (miRNAs) are small regulatory non-coding RNAs, resulting from the cleavage of long primary transcripts (pri-miRNAs) in the nucleus by the Microprocessor complex generating precursors (pre-miRNAs) that are then exported to the cytoplasm and processed into mature miRNAs. Some miRNAs are hosted in pri-miRNAs annotated as long non-coding RNAs (lncRNAs) and defined as MIRHGs (for miRNA Host Genes). However, several lnc pri-miRNAs contain translatable small open reading frames (smORFs). If smORFs present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…As mentioned previously, pri-miR-8 has been reported to encode for a small ORF that encodes for a miPEP-8, which can regulate the expression of hundreds more genes and will form a regulatory loop with miR-8 [ 182 ]. Similar ORFs have also been reported by other ncRNAs, such as lncRNA-MSA, miR-14 , and many more micro-peptides encoded in lncRNAs and circRNAs [ 145 , 183 , 184 ]. How miPEPs may have regulatory effects on the hormonal and metabolic systems and whether these miPEPs may also be regulatory targets for considerations of pathway disturbances such as insecticides all require further investigation in the future.…”
Section: Conclusion and Future Perspectivessupporting
confidence: 72%
“…As mentioned previously, pri-miR-8 has been reported to encode for a small ORF that encodes for a miPEP-8, which can regulate the expression of hundreds more genes and will form a regulatory loop with miR-8 [ 182 ]. Similar ORFs have also been reported by other ncRNAs, such as lncRNA-MSA, miR-14 , and many more micro-peptides encoded in lncRNAs and circRNAs [ 145 , 183 , 184 ]. How miPEPs may have regulatory effects on the hormonal and metabolic systems and whether these miPEPs may also be regulatory targets for considerations of pathway disturbances such as insecticides all require further investigation in the future.…”
Section: Conclusion and Future Perspectivessupporting
confidence: 72%
“…No common signature has been found among these different sORF-encoded peptides. However, so far, in plants, all tested miPEPs have been shown to act as an activator of their cognate miRNA expression contrasting with animals where only effects of sORF were detected [30,37,40].…”
Section: In Plantsmentioning
confidence: 93%
“…miPEPs have been shown to act as an activator of their cognate miRNA expression contrasting with animals where only effects of sORF were detected [30,37,40].…”
Section: Mipep Discoverymentioning
confidence: 99%
“…LINC01013 , a type of long intergenic ncRNA (lncRNA), contains smORF, and micropeptide translated from it was reported to activate myocardial fibroblasts ( 9 ). It was also reported that smORFs are also present in pri-miRNAs, which are precursors of microRNAs (miRNAs), and that smORFs regulate their expression levels in pri-miR-155 and pri-miR-497 ( 10 ). Although RN7SL1 theoretically possesses two smORFs encoding micropeptides of 7 and 16 amino acids from the 5′ side, their function is unknown.…”
mentioning
confidence: 99%